Pelatihan Pembuatan Antibacterial Hand Soap Ekstrak Daun Melinjo Kepada Santri Insan Cita Serang Banten - Ismi Farah Syarifah; Hurin Lathifatul Majidah; Bima Oktavianto (Jurnal Surya Masyarakat, 2024)
Melinjo leaves as an antibacterial hand soap have never been used. This service activity aimed to provide training in making antibacterial hand soap made from melinjo leaf extract. The method used consisted of three stages, namely partnering with Islamic boarding schools, providing education about the importance of environmental hygiene, and training in making antibacterial hand soap which was attended by students of the Insan Cita Serang (ICT) Islamic boarding school. The service activity ran successfully, which was reflected in the percentage of total participant assessments where the implementation of this activity was rated as 56% "very good" 34% "good" and only 10% rated "fairly good". The usefulness of the activity has a very high score, namely 80% "very good", 18% "good" and 2% "fairly good". Meanwhile, regarding the quality of hand soap, participants emphasized the need for improvement in terms of variations in color and fragrance of the perfume used. This service is expected to provide insight and knowledge to students regarding personal hygiene (washing hands) and skills in making antibacterial hand soap.